O impacto dos investimentos em P&D e em capex no desempenho das empresas: um estudo do setor automobilístico - Narciso, Lucas Mendonça Carlos (Universidade Federal Rural do Semi-Árido, 2019)
The objective of this work is to analyze the impact of R&D and Capital Expenditures (Capex) on sales growth and the increase in the profits of companies belonging to the automotive sector. The importance of these investments for companies is increasing, since one of the main bases for the automobile industry is traditionally innovation, and its dynamics is a direct function of R&D investment. In order to carry out this research, the employed research method consisted in the application of two models of Multiple Linear Regression (MLR), based on the report of The 2018 US Industrial R&D Investment Scoreboard, considering a total of 144 companies, for the purpose to verify the significance of R&D and Capex investments in sales growth and profit growth. The results show that investments in R&D and Capex for companies in the sector are strongly correlated with both sales and profits of firms and thus are an essential factor for the success of business dynamics.
Artigo Acadêmico
Keywords: Investimentos,; Inovaçao; Indústria automobilística; Capex; P&D; Investments,; Innovation; Automobile industry; Capex; R&D; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA